2019
DOI: 10.15252/embj.2018100825
|View full text |Cite
|
Sign up to set email alerts
|

Diverse roles of TssA‐like proteins in the assembly of bacterial type VI secretion systems

Abstract: Protein translocation by the bacterial type VI secretion system (T6SS) is driven by a rapid contraction of a sheath assembled around a tube with associated effectors. Here, we show that TssA‐like or TagA‐like proteins with a conserved N‐terminal domain and varying C‐terminal domains can be grouped into at least three distinct classes based on their role in sheath assembly. The proteins of the first class increase speed and frequency of sheath assembly and form a stable dodecamer at the distal end of a polymeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
99
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(105 citation statements)
references
References 70 publications
(131 reference statements)
4
99
2
Order By: Relevance
“…1EF) consistent with the fact that P. putida tssA1 has been reported to be essential for K1-T6SS function (31) and that in other organisms sheath formation is only observed in vivo when TssA is present (27). As it has been demonstrated that long TssA proteins from E. coli , V. cholerae and P. aeruginosa (H2-T6SS) initially localize at the baseplate and subsequently migrate at the tip of the growing sheath (27, 29), we wanted to investigate if a short TssA protein, like P. putida TssA1, exhibits a similar behavior. To monitor its localization during sheath assembly, we generated a P. putida rpoN strain expressing sfGFP-TssA1 and TssB1-mScarlet-I from their native loci.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…1EF) consistent with the fact that P. putida tssA1 has been reported to be essential for K1-T6SS function (31) and that in other organisms sheath formation is only observed in vivo when TssA is present (27). As it has been demonstrated that long TssA proteins from E. coli , V. cholerae and P. aeruginosa (H2-T6SS) initially localize at the baseplate and subsequently migrate at the tip of the growing sheath (27, 29), we wanted to investigate if a short TssA protein, like P. putida TssA1, exhibits a similar behavior. To monitor its localization during sheath assembly, we generated a P. putida rpoN strain expressing sfGFP-TssA1 and TssB1-mScarlet-I from their native loci.…”
Section: Resultsmentioning
confidence: 99%
“…Average protein sizes in kDa are given for T6SS components of each phylogenetic group and the domain architecture of TssA-like proteins is shown; the N-terminus of all TssA-like proteins forms an ImpA domain whilst their C-terminus varies (28, 29). “TagA” refers to homologues of the E. coli TagA anchor protein (30), “TagA V ” has been described as the anchor for the T6SS of V. cholerae (29), and “TagA O ”, which has a different C-terminus compared to the other two forms of TagA, has not been described before. Long TssA proteins (TssA L ) are encoded in T6SS clusters from phylogenetic groups 1 and 2, whilst short TssA proteins (TssA S ) are encoded in T6SS clusters from phylogenetic groups 3-5.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations